2017
DOI: 10.1021/acs.orglett.7b03596
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Syntheses of Heteroaryl-Substituted Imidazo[1,5-a]indole and Pyrrolo[1,2-c]imidazole via Aerobic C2–H Functionalizations

Abstract: Here we report an aerobic Pd(0) catalyzed C2-H functionalization of indoles and pyrroles with tethered N-methoxylamide as the directing group. A Pd(0)-initiated mechanism overcomes the directing or poisoning effect from a wide range of heterocycles including pyridine, pyrimidine, and thiazole. The imidazo[1,5-a]indole products are transformed to bioactive analogs after one-step manipulations, demonstrating the potential utility of this reaction in drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…A Pd(0)‐ initiated mechanism conquers the coordinating or poisoning impact from a wide scope of heterocycles including pyridine, pyrimidine, and thiazole. The imidazo[1,5‐a]indole derivatives are changed to bioactive analogs after one‐venture manipulation, exhibiting the possible practicality of this reaction in drug discovery [53] …”
Section: C−h Functionalization Of Pyrrolesmentioning
confidence: 99%
“…A Pd(0)‐ initiated mechanism conquers the coordinating or poisoning impact from a wide scope of heterocycles including pyridine, pyrimidine, and thiazole. The imidazo[1,5‐a]indole derivatives are changed to bioactive analogs after one‐venture manipulation, exhibiting the possible practicality of this reaction in drug discovery [53] …”
Section: C−h Functionalization Of Pyrrolesmentioning
confidence: 99%
“…The Yu group found that isocyanides are also active in C−H activation reactions of indole‐ N ‐carboxamides (Scheme ) . By treating indole‐ N ‐carboxamides or aza‐indole‐ N ‐carboxamides 105 and tert ‐butyl isocyanide 106 with 5 mol % Pd 2 (dba) 3 at 60 °C in methanol and air, a type of intriguing medicinally important imidazo[1,5‐a]indole and pyrrolo[1,2‐c]imidazole 107 could be constructed in good yields.…”
Section: Indole‐n‐carboxamides In C−h Activationmentioning
confidence: 99%
“…The Yu group found that isocyanides are also active in CÀ H activation reactions of indole-N-carboxamides (Scheme 27). [37] By treating indole-N-carboxamides or aza-indole-N-carboxamides 105 and tert-butyl isocyanide 106 with 5 mol % Pd 2 (dba) 3 at 60°C in methanol and air, a type of intriguing medicinally important imidazo[1,5-a]indole and pyrrolo[1,2-c]imidazole 107 could be constructed in good yields. Of note, when indole-Ncarboxamides were functionalized with various heteroaryl groups, corresponding products 110 bearing diverse heterocycles could be isolated efficiently.…”
Section: Reaction Of Indole-n-carboxamides With Other Compoundsmentioning
confidence: 99%
“…(i) Alkynes are used as unconventional C 1 synthons to fulfil an unusual [4+1] annulation, which is rare as alkynes normally act as C 2 synthons to undergo [n+2] cycloaddition in C−H annulations of indoles; (ii) a highly chemoselective [4+1] annulation, in which the competitive background reactions such as [3+2] annulation, [4+2] annulation and C−H alkenylation are inhibited; (iii) a highly regiospecific [4+1] annulation with the C−H activation occurred at C2 over C7 position of the indole and C−C/C−N bonds both formed at the distal sp hybridized carbon of the alkyne moiety; (iiii) a mild redox‐neutral transformation without the addition of any external oxidants, which results in good compatibility of various functional groups. Despite the elegant synthesis of 1 H ‐imidazo[1,5‐ a ]indol‐3(2 H )‐ones from indoles with hazardous diazo compounds, [11a,16] 4‐hydroxyphenylboronic acid under silver oxidants [17] or isocyanides under air oxidation, [18] our method stands as the first example of 1 H ‐imidazo[1,5‐ a ]indol‐3(2 H )‐one synthesis via a redox‐neutral Rh(III)‐catalyzed [4+1] annulation of N ‐carbamoyl indoles exploiting alkynes as C 1 synthons. Regarding the large occurrence of the 1 H ‐imidazo[1,5‐ a ]indol‐3(2 H )‐one motif in pharmaceutical agents (Figure 1), [19] our approach is quite attractive as it offers a facile and rapid access to highly functionalized 1 H ‐imidazo[1,5‐ a ]indol‐3(2 H )‐ones from readily available materials through Rh(III)‐catalyzed chemo‐ and regioselective [4+1] annulation.…”
Section: Introductionmentioning
confidence: 99%